Investigation on Informal Worker: Case Study in Lampung Province, Indonesia - Dinar Melani Hutajulu; Fitrah Sari Islami; Lucia Rita Indrawati (Jurnal REP (Riset Ekonomi Pembangunan), 2026)
The issue of job informality is an important aspect of the labor market. The higher informal workers, indicates the higher number of vulnerable workers with low wages and poverty. Lampung Province has the highest level of informal employment in Sumatra and higher than the national average level. Even some research raises job informality, contradictions in findings across different regions and countries still exist. This study used binary logistic regression to analyze the determinants of informal employment in Lampung Province. The data were cross-sectional data on February 2025 National Labor Force Survey (SAKERNAS) conducted by Statistics Indonesia (BPS), with a total of 5,783 observations. This research find that age, marital status, geographic location, and technology provide significant positive opportunities for job informality. Gender, education, and disability conditions have a significant negative impact on the informality of employment. It can be concluded that the increasing age encourages individuals to get jobs in the informal sector. Marriage provides a great opportunity to work in the informal sector, especially for individuals with economic demands. In fact, women in Lampung have a higher chance of working in the informal sector. Lower education increases opportunities for the informal sector, while higher education reduces opportunities. Technology still provides great opportunities for work, especially informal sector jobs that require technological knowledge. Another fact shows that disability conditions provide fewer opportunities for the informal sector.